Phases Transitions in a Cross-Cavity Quantum Rabi Model Possessing PT Symmetric Structure - Wang, Ning; Gong, Zhi-Rui; Lu, Jing; Zhou, Lan (Frontiers in Physics, 2019)
We investigated the quantum phase transitions in a cross-cavity quantum Rabi model which possesses the parity-time symmetric structure. Both the open quantum Rabi phase transition and the spontaneous parity-time symmetry breaking exist simultaneously in such system. The competition between these two phase transitions produces the plentiful phase diagram. We also propose the detection of the open cross-cavity quantum Rabi phase transition through the measurement of the parity-time symmetric or asymmetric states, which shed light on the precise detection of the few-body phase transition.